Professional Adaptation of Young Teachers in A Preschool Educational Organization (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to management issues as a form of organizational and pedagogical conditions that affect the adaptation of young professionals in a preschool educational organization. The conditions for managing the gradual entry of a young specialist into the teaching profession in the context of the introduction of a professional standard are described.